METAL-ION IMPRINTED POLYMERS FOR SEPARATION, PRE-CONCENTRATION AND PD(II) ION ANALYSIS - Windyasari, Intan
Palladium, a member of Platinum Group Metals – PGMs, has important roles in industry advancements, particularly automotive and electronic industries, and industries that produce dental alloy equipment. To maintain a continues supply of palladium, various techniques to extract palladium have been developed. To date, efforts are still ongoing to discover reliable methods with high selectivity to extract palladium from real samples.